Status Gizi, Pola Konsumsi, Aktivitas Fisik, Riwayat Kesehatan dan Fenotip Wanita Muda Obese di Kota Bandung: Nutritional Status, Eating Patterns, Physical Activity, Health and Phenotype History of Obese Young Women in Bandung City - Novitasari, Putri; Rimbawan, Rimbawan; Hardinsyah, Hardinsyah; Riyadi, Hadi (Amerta Nutrition, 2025)
Background: The incidence of obesity in Bandung City is rising. The prevalence of obesity among women surpasses that of men, with a notable rise observed in the young adult demographic. Objectives: This study assessed the nutritional status, dietary habits, physical activity, health history, and phenotype of young obese women in Bandung City. Methods: This mixed-method design involved 88 obese individuals (body fat percentage >35%) aged 18-25 years of Sundanese ethnicity. The research was carried out from August to November 2023. The obtained data encompassed general subject characteristics, anthropometric measurements, body composition, dietary intake and physical activity information, health history, and phenotypic data. Comprehensive interviews were performed concerning dietary habits, physical activity, phenotypic history, nutritional status, and health history. Results: The participants' average age and body weight were 20.3 years and 81.5 kilograms, respectively. The average total fat percentage (%BF) was 38.3%. Occupation (p-value=0.033), weight (p-value=0.001), body mass index (p-value=0.001), waist circumference (p-value=0.001), hip circumference (p-value=0.001), visceral fat (p-value=0.001), resting metabolism (p-value=0.001), and energy (p-value=0.009), fat (p-value=0.043), and carbohydrate (p-value=0.021) intake were associated with total body fat. Conversely, the subject's physical activity, personal and familial history of chronic diseases, development of obesity, and parental obesity history exhibited no correlation with the subject's total body fat (p-value≥0.05). Conclusions: The subject’s occupation, body weight, body mass index, waist and hip circumference, visceral fat, resting metabolism, energy, fat, and carbohydrate intake were correlated with the subject's total body fat.